Walking parameters of older adults from a lower back inertial measurement unit, a 6-year longitudinal observational study - Elshehabi, Morad; Del Din, Silvia; Hobert, Markus A.; Warmerdam, Elke; Sünkel, Ulrike; Schmitz-Hübsch, Tanja; Behncke, Lisa Marie; Heinzel, Sebastian; Brockmann, Kathrin; Metzger, Florian G.; Schlenstedt, Christian; Rochester, Lynn; et al. (Frontiers in Aging Neuroscience, 2022)
Gait changes during aging and it differs between genders. Inertial measurement units (IMUs) enable accurate quantitative evaluations of gait in ambulatory environments and in large populations. This study aims to provide IMU-based gait parameters’ values derived from a large longitudinal cohort study in older adults. We measured gait parameters, such as velocity, step length, time, variability and asymmetry, from straight, self-paced 20-meter walks in older adults (four visits; 715/1065/1009/922 participants) every second year over six years using an IMU at the lower back. Moreover, we calculated the associations of gait parameters with gender and age (ANOVA) and the contribution of confounding factors to gait (multiple regression). Parameters associated with age underwent longitudinal evaluation using generalized estimating equations. Women showed lower gait velocity, step length, step time, stride time, swing time and stance time, and higher step length variability and asymmetry, compared to men. Confounding factors explained up to 21.9% of the variance of gait and are more relevant in men in their 6th decade. Health state, body mass index and the tendency to fall influenced gait velocity, a parameter linked to morbidity in older adults. Longitudinal analyses suggest continuous yearly changes in men in gait velocity and step time starting from the 7th decade and step length from the 8th. Gait changes in women started in the 8th decade, affecting step time. Altogether, our large longitudinal dataset from an IMU at the lower back provides useful information about gait changes in older age.